Impact of Slice Thickness on the Predictive Value of Lung Cancer Screening Computed Tomography in the Evaluation of Coronary Artery Calcification - Jared L. Christensen; Esseim Sharma; Anastassia Y. Gorvitovskaia; Jerome P. Watts; Maen Assali; Jade Neverson; Wen‐Chih Wu; Gaurav Choudhary; Alan R. Morrison (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background Image reconstruction thickness may impact quantitative coronary artery calcium scoring (CACS) from lung cancer screening computed tomography (LCSCT), limiting its application in practice. Methods and Results We evaluated Agatston‐based quantitative CACS from 1.25‐mm LCSCT and cardiac computed tomography for agreement in 87 patients. We then evaluated Agatston‐based quantitative CACS from 1.25‐, 2.5‐, and 5.0‐mm slice thickness LCSCT for agreement in 258 patients. Secondary analysis included the impact of slice thickness on predictive value of 4‐year outcomes. Median age of patients who underwent 1.25‐mm LCSCT and cardiac computed tomography was 63 years (interquartile interval, 57, 68). CACS from 1.25‐mm LCSCT and cardiac computed tomography demonstrated a strong Pearson correlation, R=0.9770 (0.965, 0.985), with good agreement. The receiver operating characteristic curve areas under the curve for cardiac computed tomography and LCSCT were comparable at 0.8364 (0.6628, 1.01) and 0.8208 (0.6431, 0.9985), respectively (P=0.733). Median age of patients who underwent LCSCT with 3 slice thicknesses was 66 years (interquartile interval, 63, 73). Compared with CACS from 1.25‐mm scans, CACS from 2.5‐ and 5.0‐mm scans demonstrated strong Pearson correlations, R=0.9949 (0.9935, 0.996) and R=0.9478 (0.9338, 0.959), respectively, though bias was largely negative for 5.0‐mm scans. Receiver operating characteristic curve areas under the curve for 1.25‐, 2.5‐, and 5.0‐mm scans were comparable at 0.7040 (0.6307, 0.7772), 0.7063 (0.6327, 0.7799), and 0.7194 (0.6407, 0.7887), respectively (P=0.6487). When using individualized high‐risk thresholds derived from respective receiver operating characteristic curves, all slice thicknesses demonstrated similar prognostic value. Conclusions Slice thickness is an important consideration when interpreting Agatston CACS from LCSCTs. Despite the absence of ECG gating, it appears reasonable to report CACS from either 1.25‐ or 2.5‐mm slice thickness LCSCT to help stratify cardiovascular risk. Conversely, 5.0‐mm scans largely underidentify calcium, limiting practical use within the established CACS values used to categorize cardiovascular risk.